Design of Magnetron for Beamforming - Chun-Hsi Su; Meng-Xun Ku (Engineering Proceedings, 2025)
The design of a vane-type magnetron with a resonant frequency in the megahertz range is presented in this article. The initial dimensions are determined based on magnetron empirical formulas. CST Studio Suite was used to simulate a series of magnetron behaviors, including eigenmode analysis and particle-in-cell (PIC) simulations. The relationship between volume and frequency results in a significantly large magnetron size for MHz frequencies. Considering manufacturing convenience and cost factors, the magnetron was simplified from its initial design, and the operating frequencies were compared, revealing a difference of about 40 MHz. The simulated frequency was 193 MHz, and the magnetron field patterns were simulated using CST. In the simulation, a horn antenna-like structure was employed to reduce the magnetron’s half-power beamwidth (HPBW), narrowing it from 101 to 50°. The result of this study can be used for beam focusing.